Uwarunkowania prospektywneao modelu rodziny w opinii młodzieży polskiej w wieku matrymonialnym - Ignatczyk, Walentyna (Wydział Prawa i Administracji UAM, 1985)
The article presents partial results of the survey of family attitudes of the Polish youth which was in age of matrimony at the moment of study. Surveying family attitudes of youth in an interdisciplinary approach is conducted by the Institute of Statistics and Demography of the Academy of Economics in Poznań. The family attitudes of youth are understood to be their relation to concluding a matrimony, number of children to have, and conditioning of marriage and procreational decisions. The identification of factors conditioning a future family behavior of youth was found to be essential from the viewpoint of the general task of the survey. The identification of conditioning carried out confirmed the view that the Polish youth is intent on creating a family family ambitions are occupying the first place among life ambitions. Professional, material, financial, social and other ambitions are treated by youth as requisites to fulfill family ambitions. The detailed results of identifying factors conditioning the conclusion of matrimony are found in the eight tables. The youth prefers a one-child, two-children model of family. It can be inferred from the survey that a three-children model of family would be preferred if the conditions securing a better living standard of married couples were secured and the emotional bond between spouses was still lasting. Taking account of the youth life aspirations — in face of the threatening deformations in demographic processes — is necessary in. the actions promoting development of future Polish family.
Conditioning of a prospective family model in opinions of the Polish youth in age of matrimony